Twelve tips on setting up a new medical school. (2013) - Cookson, John
Abstract : Background : Not many set up a new medical school, so those that do usually do it only once. Thus most have no personal previous experience to guide them. Aim : To give those setting up a new school some broad issues to think about as they set about their task. Methods : The tips were derived from personal experience in the UK and in Africa. Results: The 12 tips identified are engage closely with the parent university from the outset; decide what the medical school is going to concentrate on first; agree on the overall aim of the school; decide who 'owns' the course; agree on the type of pedagogy to be employed; ensure good alignment between the aims, outcomes, learning framework and assessment; plan the assessment along with the rest of the course; make sure the school facilities are sufficient and appropriate to support the aims of the course; appoint the right staff; plan the research programme early; plan the co-ordination between the university and the health services at all levels; communicate, communicate, communicate. Conclusion : It is hoped that these suggestions will be widely applicable to different contexts and assist those in the exciting task of setting up a new school.